Ecumenical dialogue on Reconciliation : Belgrade, 19-22 February 1996, Conference of European Churches, Theological Faculty, Serbian Orthodox Church (Conference of European Churches, 1996)
"Pastors and theologians from the Orthodox, Roman Catholic and Protestant Churches, coming from all parts of Europe as well as North America, met for four days in Belgrade to explore the theme of reconciliation ..."--Cover p.4.